Effects of exercise training on left ventricular systolic and diastolic function after myocardial infarction: systematic review and meta-analysis - Zhang, XiaoMing; Mi, Yao; Ding, Mingwang; Gao, Xin (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesExercise training is a rehabilitative approach to improve cardiac function in patients with myocardial infarction. However, evidence on the effectiveness of exercise training in these patients remains limited. In this meta-analysis, we aim to evaluate the extent to which exercise training improves cardiac function in patients with myocardial infarction.MethodsWe conducted a systematic search of the PubMed, Embase, Cochrane Library, and Web of Science databases to compare cardiac function in myocardial infarction patients who received exercise training combined with standard pharmacological therapy. The cardiac function indicators evaluated included: LVEF, E, E/A, LVIDd, LVIDs, NT-proBNP, E' septal, GLS, and LVMI.ResultsThe final analysis included 12 studies with a total of 922 patients. Compared with the standard treatment group, exercise training significantly improved LVEF (MD = 3.99, 95% CI: 1.30–6.68) and E (MD = 3.86, 95% CI: 1.33–6.39) in myocardial infarction patients, while showing no significant improvement in the remaining indicators.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024571194, PROSPERO (CRD42024571194).